2018
DOI: 10.1093/humrep/dey366
|View full text |Cite
|
Sign up to set email alerts
|

A risk prediction model of sperm retrieval failure with fine needle aspiration in males with non-obstructive azoospermia

Abstract: STUDY QUESTIONCan we predict the risk of sperm retrieval failure among men with non-obstructive azoospermia (NOA) before they undergo fine needle aspiration (FNA)?SUMMARY ANSWEROur model, which includes FSH level, age and testicular volume as variables, can predict the risk of sperm retrieval failure with FNA.WHAT IS KNOWN ALREADYCombined with ICSI, testicular sperm aspiration (TESA) can enable patients with NOA to have their own genetic offspring. Nearly all reproductive medicine centres in China have applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…The binary logistic regression models were built for biomarkers based on the backward-selected metabolites. The area under the receiver operating characteristic (ROC) curves (AUC) were used to assess the predictive ability of models [ 10 , 32 ]. The schematic workflow of statistical analysis is listed in Figure S1 .…”
Section: Methodsmentioning
confidence: 99%
“…The binary logistic regression models were built for biomarkers based on the backward-selected metabolites. The area under the receiver operating characteristic (ROC) curves (AUC) were used to assess the predictive ability of models [ 10 , 32 ]. The schematic workflow of statistical analysis is listed in Figure S1 .…”
Section: Methodsmentioning
confidence: 99%
“…The variables included in the formula were age, FSH value and testicular volume with failure risk cut-off value of 64.61%. The sensitivity and specificity of this formula was 0.677 and 0.863 respectively ( 8 ). Based on the formula, the risk of failure of our case was 79.25%, which means there was a high chance of retrieval failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study above only mentioned the formula to be used as a risk prediction for FNA Mapping as a sperm retrieval method, not a guiding method. Moreover, the study also did not include the AZFc microdeletion when formulating the equation, thus the actual risk of sperm retrieval failure might be different ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al . 99 developed a multivariable logistic model to predict the likelihood of sperm retrieval failure using TESA in NOA men. The authors reported that the predictive model had an AUC of 82.3% with a sensitivity of 0.677 and a specificity of 0.863.…”
Section: Predictive Modellingmentioning
confidence: 99%